Model Tajuk Jati (Tectona Grandis L.f) dari Berbagai Famili pada Uji Keturunan Umur 9 Tahun - Jany T. Raharjo; Ronggo Sadono (Jurnal Ilmu Kehutanan, 2008)
Crown Model on Several Family of   9 years old  of Teak (Tectona grandis L.f) Progeny TrialCrown plays an important role in regulating the rate of tree growth through the photosynthesis process. Furthermore it can be used to measure stand density and to determine the availability of growing space. Because of the difficulty  and time consuming in direct crown measurement, the development of crown model is needed. The objectives of this study were to develop crown models of teak (Tectona grandis) of 9 years old from selected open pollinated families and to identifi) the variations of crown models among them.The study was conducted in an open pollinated progeny test located at the compartment 49a, RPH Sidowayah, BKPH Kedunggalar, KPH Ngawi. The experimental unit was family. Five families with the best average of stem diameter at breast height were selected as samples. Crown models were developed and variations of crown model were tested with analysis of variance.The crown model of teak can be divided into two sections. The upper crown representing the light crown section followed parabolic model while the under crown representing the shaded crown section followed linear model. No differences in crown model were found among families. The proposed models are:light crown section, paraboloid : Rl =1.91 * hl0.33shaded crown section, linear .. Rs = -0.75 + 0.57 hswhere Rl is light crown radius (m), hl is the height of light crown section (m), Rs is shaded crown radius (m) and hs is the height of shaded crown section (m)